Training load in relation to loading and unloading phases of training - Australian Institute of Sport (2021)
This can be used by coaches, performance support team members and organisations in the national high performance sport system as a resource to guide conversations relating to holistic approaches to well-periodised and individualised training load planning following unloading. In 2015, the first version of this was published as part of a multi-disciplinary project including the AIS Disciplines of Medicine, Strength and Conditioning, Sports Nutrition, Physiology, and Physical Therapies. Version 2 has been developed in consultation with representatives from the National Institute Network and National Sporting Organisations with input from experts in the wider professional sport and university sectors.